Performance Evaluation of the AuRa Consensus Algorithm for Digital Certificate Processes on the Ethereum Blockchain - Arifin, Robiah; Bakar, Wan Aezwani Wan Abu; Man, Mustafa; Kadir, Evizal Abdul (International journal of advanced computer science & applications, 2024)
The blockchain serves as a distributed database where data is stored across different servers and networks. It encompasses various types, with Bitcoin, Ethereum, and Hyperledger being notable examples. To safeguard the security of data transactions on the blockchain, it relies on a consensus algorithm. This algorithm facilitates agreement among nodes within the network. There are multiple types of consensus algorithms, each possessing unique specialties and characteristics. This paper drives into the examination of specific Authority Round, here claimed as AuRa_ori consensus algorithm. The AuRa_ori is a specific type of PoA consensus mechanism used primarily in private or permission blockchain networks. It works by having a set of trusted validators take turns in a round-robin fashion to produce new blocks. It is supported by Parity and Ethereum Clients. AuRa_ori assumes that all the authority nodes are synchronised and honest on every transaction process. In AuRa_ori, every transaction process will execute the four phases i.e., assigning of a new leader, proposing a block, commencing agreement and finally, the phase of committing. However, there exist some discrepancies in some of the phases. In response to the scenario, this paper presents a thorough discussion on the vulnerabilities adhered in AuRa phases in transaction execution by focusing on the first phase of assigning a new leader and the third phase, namely the agreement. The vulnerabilities are subjected to the risk of impacting the performance of Transaction Speed Per Second (TPS), Transaction Throughput (TGS), Percentage Decrease (PD) of TPS and Percentage Increase (PI) of TGS. The new improved method, named AuRa_v1 is parallel presented to overcome the vulnerabilities of AuRa_ori at the selected phases. It aims to increase the TPS and to calculate the PD in transaction process using the Ethereum private blockchain systems. The implementation used three set of data scroll certificate. The result showed that the AuRa_v1 able to decrease the TPS almost 30% based on difference number set of data.